Peran Digital Integrated Marketing Communication terhadap Loyalitas Konsumen Produk Makanan di TikTok - Afirsta Marselia Purana; Putranto, Teguh Dwi (MEDIASI Jurnal Kajian dan Terapan Media, Bahasa, Komunikasi, 2025)
TikTok has become an effective digital marketing communication channel that also serves as a powerful advertising tool, especially for attracting the attention of Generation Z. TikTok allows sellers to present promotional material in an engaging way. TikTok facilitates the promotion of food products using attractive images, customer interaction through comments or live streams, making the message more relevant. This study aims to determine the role of Digital Integrated Marketing Communication (IMC) in increasing consumer loyalty to food products on TikTok. The case study focuses on viral brands such as Cimood by Maudy, Tahu Huha by Farida Zulfa, and Pisang Ijo Cendana. This study uses a literature review method that examines previous studies related to Digital Integrated Marketing Communication (IMC) in increasing consumer loyalty to food products on TikTok. The findings indicate that TikTok is effective as a marketing medium due to its ability to widely disseminate content through adaptive algorithms, as well as facilitating two-way interaction between businesses and consumers. The role of influencers, storytelling strategies, and educational and entertaining content are key factors in building emotional connection and consumer loyalty. TikTok is not only a platform for entertainment but also a strategic tool within the dynamic digital marketing ecosystem. This research recommends the creative and integrated use of TikTok in IMC strategies to enhance the competitiveness of food businesses in the digital age.